2015
DOI: 10.1016/j.ymben.2015.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Futile cycling increases sensitivity toward oxidative stress in Escherichia coli

Abstract: Reactive oxygen species (ROS) are toxic molecules utilized by the immune system to combat invading pathogens. Recent evidence suggests that inefficiencies in ATP production or usage can lead to increased endogenous ROS production and sensitivity to oxidative stress in bacteria. With this as inspiration, and knowledge that ATP is required for a number of DNA repair mechanisms, we hypothesized that futile cycling would be an effective way to increase sensitivity to oxidative stress. We developed a mixed integer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 70 publications
(112 reference statements)
5
63
0
Order By: Relevance
“…However, the mechanism bridging protease activity to NO• defense in both of these studies was not explored, though it was speculated that the protease could be responsible for digesting NO•-damaged proteins that may otherwise accumulate to toxic levels within the cell [10]. In this work, not only did we identify a novel NO•-defensive role for ClpP in Ensemble modeling is a methodology that has previously been employed to computationally explore systems for which uncertainty exists in parameter values and/or network structure [45][46][47][48][49][50][51][52][53][54][55][56]. For example, Wang and Hatzimanikatis used a Monte Carlo method to address kinetic parameter uncertainty in a metabolic control analysis (MCA) study of Saccharomyces cerevisiae central carbon metabolism, and identified major differences in control schemes between batch and chemostat culturing conditions [46].…”
Section: Discussionmentioning
confidence: 98%
“…However, the mechanism bridging protease activity to NO• defense in both of these studies was not explored, though it was speculated that the protease could be responsible for digesting NO•-damaged proteins that may otherwise accumulate to toxic levels within the cell [10]. In this work, not only did we identify a novel NO•-defensive role for ClpP in Ensemble modeling is a methodology that has previously been employed to computationally explore systems for which uncertainty exists in parameter values and/or network structure [45][46][47][48][49][50][51][52][53][54][55][56]. For example, Wang and Hatzimanikatis used a Monte Carlo method to address kinetic parameter uncertainty in a metabolic control analysis (MCA) study of Saccharomyces cerevisiae central carbon metabolism, and identified major differences in control schemes between batch and chemostat culturing conditions [46].…”
Section: Discussionmentioning
confidence: 98%
“…This could lead to a significant increase in macromolecule damage. Accordingly, we found that ΔpBClin15 exhibited (i) a significant increase in lag phase, which represents the rejuvenation of bacterial life that accompanies the repair of oxidative damage [49], and (ii) a decreased tolerance to exogenous oxidant [41,50]. Finally, by increasing the modularity of central metabolic pathways, pBClin15 may increase the ATP-dependent ability of the cell to repair the damage caused by endogenous oxidative stress during aerobic growth and increase the cell's ability to cope with additional oxidative stress.…”
Section: Detailed Analysis Of the Whole Cell Proteomementioning
confidence: 93%
“…(36) simultaneously leads to increased ion permeability of the membrane that effectively increases the ATP usage needed to maintain constant essential cellular functions and ion homeostasis. Thus, by increasing the proton permeability of the yeast membranes (37), AmB raises the activity of Pma1, the H ϩ -ATPase pump, and other futile cycles that deplete ATP, leading to a higher level of ROS production that promotes oxidative killing (38). ATP depletion is also enhanced in Candida albicans by the AmB-induced shift from fermentation to respiration (30), a finding that is consistent with the observation that, in respiration, H ϩ -ATPase function is one of the major ATPconsuming pathways whose level is increased (39).…”
Section: The Molecular Mechanism Of Signal Transduction Induced By Thmentioning
confidence: 99%